2002
DOI: 10.1016/s1097-2765(02)00741-4
|View full text |Cite
|
Sign up to set email alerts
|

MLL Targets SET Domain Methyltransferase Activity to Hox Gene Promoters

Abstract: MLL, the human homolog of Drosophila trithorax, maintains Hox gene expression in mammalian embryos and is rearranged in human leukemias resulting in Hox gene deregulation. How MLL or MLL fusion proteins regulate gene expression remains obscure. We show that MLL regulates target Hox gene expression through direct binding to promoter sequences. We further show that the MLL SET domain is a histone H3 lysine 4-specific methyltransferase whose activity is stimulated with acetylated H3 peptides. This methylase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
871
1
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 958 publications
(910 citation statements)
references
References 48 publications
27
871
1
5
Order By: Relevance
“…29 Transcription factors such as p53 and CTNNB1(b-catenin) are most likely to recruit the MLL complex to initiate RNA synthesis, 26,30 and specific genes, such as the HOX genes, seem to be more dependent on the MLL complex for chromatin modification during transcription than others. 31,32 In MLL rearrangements the breakpoint in MLL is highly conserved and all fusion partners are fused in frame, leading to a gain of function of the MLL complex. The MLL fusion most likely disrupts the MLL complex, leading to inappropriate expression of specific HOX genes, that is, HOXA4, HOXA5, HOXA9 and HOXA10, in pediatric MLL-rearranged AML.…”
Section: Etiology Of Mll Rearrangementsmentioning
confidence: 99%
“…29 Transcription factors such as p53 and CTNNB1(b-catenin) are most likely to recruit the MLL complex to initiate RNA synthesis, 26,30 and specific genes, such as the HOX genes, seem to be more dependent on the MLL complex for chromatin modification during transcription than others. 31,32 In MLL rearrangements the breakpoint in MLL is highly conserved and all fusion partners are fused in frame, leading to a gain of function of the MLL complex. The MLL fusion most likely disrupts the MLL complex, leading to inappropriate expression of specific HOX genes, that is, HOXA4, HOXA5, HOXA9 and HOXA10, in pediatric MLL-rearranged AML.…”
Section: Etiology Of Mll Rearrangementsmentioning
confidence: 99%
“…It is believed that Mll controls Hox gene expression by binding to Hox regulatory elements and association with other transcriptional regulators. Indeed, MLL binding to the promoters of HOXA9 and Hoxc8 was described recently [Milne et al, 2002;Nakamura et al, 2002]. Overexpression of some Hox genes, including Hoxa9, has been linked to leukemia in mouse models.…”
Section: Wild-type Mll Functionmentioning
confidence: 99%
“…Methylation of the lysine residues on histone tails is part of the proposed histone code in which different histone modifications direct the recruitment of transcriptional regulators, ultimately exerting an influence on gene expression [Jenuwein and Allis, 2001]. While the initial studies failed to confirm such enzymatic function in the MLL SET domain, more recently two groups have shown that mouse and human MLL SET domains are indeed able to methylate lysine residues on histone tails [Milne et al, 2002;Nakamura et al, 2002]. The specificity of the MLL SET domain is for lysine 4 (K4) on histone H3.…”
Section: Many Pieces Of the Puzzlementioning
confidence: 99%
“…Several reports have detailed how deregulation of methylation can be the direct cause or result of cellular dysfunction. For example, in certain cancers, hyper-and hypomethylation of specific regions of DNA by DNMTs and rearrangement of chromatin due to HMTs are observed routinely and serve to silence and activate genes related to cell growth and malignancy [11][12][13][14][15][16].The study of methyltransferase activity and its regulation continues to be an important and promising area of research in fields from oncology to neurology. Thus, there currently is a demand for the ability to screen large compound libraries to identify and optimize small molecules that modulate methyltransferase activity.…”
mentioning
confidence: 99%
“…Several reports have detailed how deregulation of methylation can be the direct cause or result of cellular dysfunction. For example, in certain cancers, hyper-and hypomethylation of specific regions of DNA by DNMTs and rearrangement of chromatin due to HMTs are observed routinely and serve to silence and activate genes related to cell growth and malignancy [11][12][13][14][15][16].…”
mentioning
confidence: 99%